Characteristic energy scales in CePdAl. Issue 3 (27th February 2013) - Woitschach, Sarah; Stockert, Oliver; Koza, Michael Marek; Fritsch, Veronika; von Löhneysen, Hilbert; Steglich, Frank
Abstract We report on inelastic neutron scattering experiments that were carried out on single‐crystalline CePdAl, which is a heavy fermion system with hexagonal crystal structure and is close to an antiferromagnetic quantum critical point. The measurements yield information on the crystalline‐electric‐field (CEF) excitations and quasielastic spin fluctuations. Two excited CEF levels have been detected at ≈240 K and >400 K. A broad quasielastic magnetic signal could be observed, yielding a Kondo temperature TK = 5 K that agrees with the result from thermodynamic measurements.